Epidermal Growth Factor and Intestinal Barrier Function. (25th July 2016) - Tang, Xiaopeng; Liu, Hu; Yang, Shufen; Li, Zuohua; Zhong, Jinfeng; Fang, Rejun
Abstract : Epidermal growth factor (EGF) is a 53-amino acid peptide that plays an important role in regulating cell growth, survival, migration, apoptosis, proliferation, and differentiation. In addition, EGF has been established to be an effective intestinal regulator helping to protect intestinal barrier integrity, which was essential for the absorption of nutrients and health in humans and animals. Several researches have demonstrated that EGF via binding to the EGF receptor and subsequent activation of Ras/MAPK, PI3K/AKT, PLC- γ /PKC, and STATS signal pathways regulates intestinal barrier function. In this review, the relationship between epidermal growth factor and intestinal development and intestinal barrier is described, to provide a better understanding of the effects of EGF on intestine development and health.